BODY HEIGHT INCREASED OF NEW STUDENT OF UDAYANA UNIVERSITY 1990 AND 2000 - Arya Sena, I Gede; Suyasning, HI; Sutjana, IDP (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 2, No. 1 Maret 2008, 2012)
Changes in body height have been affected by many factors among others genetic,health, hormonal, social economic, exercise, nutrition intake, etc. It was due toimportance physiology parameter to determine growth and nutrition conditioned of thepeople. Income per capita in West Countries higher than Asian includes Indonesian.Some approximates of mean the body height were done on Norwegian and USA isincreasing, up to 13 mm and 10 mm until ten years. Further, the assumption of nutritionintake is increasing for mothers and infant, unanimously increasing of Bali (Indonesian)gross domestic product until 1975 - 1980. So that body height has been increased to nextgeneration. A total of 3.917 subject on 1990, divided in to 2.340 male and 1.577 female students and 1.218 subject on 2000 divided in to 525 male and 693 female students. Theresult showed that body height has been increased for male and female 22,1 mm; 19.88mm, respectively.
Keywords: body stature, gross domestic product, nutrition intake